Aviation Expert System / Nimalan Christopher Ananda Rajah - Nimalan Christopher , Ananda Rajah (2002)
The aviation expert system is a stand-alone rule-based prescription expert system. Prescription systems recommend solutions to given system malfunction. The aviation expert system is an artificial intelligence system developed using a logic programming language. The primary objective of this system is to advise trainee pilots on the course of action to take when dealing with a failure situation in simulation cockpits. It receives input from the user and provides counter measures based on the input. The problem-solving approach used in this system is rule-baesd reasoning. A rule is a form of procedural knowledge, facts, and problem solving strategic to draw conclusions. Expert systema model the reasonning process of humans using a techique called inference, which is the process of deriving new information from known information.The author hopes that the aviation expert system will the disadvantages of the current system being employed by airline companies around the world.